The microbiome of tunnels in hidradenitis suppurativa patients. (6th May 2019) - Ring, H.C.; Sigsgaard, V.; Thorsen, J.; Fuursted, K.; Fabricius, S.; Saunte, D.M.; Jemec, G.B.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease defined by recurrent nodules, tunnels and scarring involving the intertriginous regions. Recent next‐generation sequencing (NGS) studies suggest genera such as Prevotella spp., Peptoniphilus spp. and Porphyromonas spp. are associated with chronic and early HS lesions. However, a systematic investigation of the bacterial microbiome in HS tunnels remains unexplored using NGS. Objective: We aimed to investigate the bacterial composition of the luminal white gelatinous material found in HS tunnels using NGS. Methods: An exploratory study of patients with diagnosis of HS ( n  = 32) with tunnels. The tunnels were present either in the groin ( n  = 17) or in the axilla ( n  = 15). During deroofing of the tunnels, a sterile E‐swab was taken of the luminal gelatinous material. The samples were investigated using NGS targeting 16S ribosomal RNA. Results: The skin microbiome was characterized in 32 HS patients. Overall, five microbiome types were identified: Porphyromonas spp. (type I), Corynebacterium spp., (type II), Staphylococcus spp. (type III), Prevotella spp. (type IV) and Acinetobacter spp (type V). Porphyromonas spp. (type I) and Prevotella spp. (IV) were the most frequent genera found the tunnels. Conclusion: This study points to a potential association between the presence of certain anaerobic bacteria ( Porphyromonas spp., Prevotella spp.) and HS tunnels. It may be speculated that these two genera are associated with the pathogenesis in HS either as drivers or as biomarkers.